Evaluation of two singleplex reverse transcription-Insulated isothermal PCR tests and a duplex real-time RT-PCR test for the detection of porcine epidemic diarrhea virus and porcine deltacoronavirus - Zhang, Jianqiang (J Virol Methods, 2016)
Recent outbreaks of porcine epidemic diarrhea virus (PEDV) and porcine deltacoronavirus (PDCoV) in multiple countries have caused significant economic losses and remain a serious challenge to the swine industry. Rapid diagnosis is critical for the implementation of efficient control strategies before and during PEDV and PDCoV outbreaks. Insulated isothermal PCR (iiPCR) on the portable POCKIT™ device is user friendly for on-site pathogen detection. In the present study, a singleplex PEDV RT-iiPCR, a singleplex PDCoV RT-iiPCR, and a duplex PEDV/PDCoV real-time RT-PCR (rRT-PCR) commercial reagents targeting the M gene were compared to an N gene-based PEDV rRT-PCR and an M gene-based PDCoV rRT-PCR that were previously published and used as reference PCRs. All PCR assays were highly specific and did not cross react with other porcine enteric pathogens. Analytical sensitivities of the PEDV RT-iiPCR, PDCoV RT-iiPCR and duplex PEDV/PDCoV rRT-PCR were determined using in vitro transcribed RNA as well as viral RNA extracted from ten-fold serial dilutions of PEDV and PDCoV cell culture isolates. Performance of each PCR assay was further evaluated using 170 clinical samples (86 fecal swabs, 24 feces, 19 intestines, and 41 oral fluids). Compared to the reference PEDV rRT-PCR, the sensitivity, specificity and accuracy of the PEDV RT-iiPCR were 97.73%, 98.78%, and 98.24%, respectively, and those of the duplex PEDV/PDCoV rRT-PCR were 98.86%, 96.34%, and 97.65%, respectively. Compared to the reference PDCoV rRT-PCR, the sensitivity, specificity and accuracy of the PDCoV RT-iiPCR were 100%, 100%, and 100%, respectively, and those of the PEDV/PDCoV duplex rRT-PCR were 96.34%, 100%, and 98.24%, respectively. Overall, all three new PCR assays were comparable to the reference rRT-PCRs for detection of PEDV and/or PDCoV. The PEDV and PDCoV RT-iiPCRs are potentially useful tools for on-site detection and the duplex PEDV/PDCoV rRT-PCR provides a convenient method to simultaneously detect the two viruses and differentiate PEDV from PDCoV.